Is shame responsible for maladaptive daydreaming among grandiose and vulnerable narcissists? A general population study. (May 2023) - Ghinassi, Simon; Fioravanti, Giulia; Casale, Silvia
Abstract: Previous studies suggest that narcissists are tied to fantasies that bolster their self-esteem when they feel threatened. Vulnerable narcissists, in particular, might be at risk of developing maladaptive daydreaming (MD) in that they tend to experience high levels of shame, which turns out to be closely associated with MD. We hypothesized an effect of grandiose and vulnerable narcissistic traits on MD, which was expected to be mediated by shame levels among vulnerable narcissists. A community sample of 357 participants (66.70 % females; M age = 32.17 ± 13.41) was recruited. The assessed structural model produced adequate fit to the data [χ 2 = 230.77, df = 100, p < .001; RMSEA = 0.06 (90 % C.I. = 0.05–0.07), CFI = 0.96, SRMR = 0.06]. Vulnerable narcissism predicted MD through characterological shame. Conversely, it seems that bodily shame is not dealt with MD among vulnerable narcissists. Grandiose narcissism was associated with MD to a lesser extent, and MD seems to be a dysfunctional but effective strategy to reduce characterological shame for grandiose narcissists - whilst the opposite seems to be true for vulnerable narcissists. Individuals with vulnerable narcissistic traits may benefit from clinical interventions that address their tendencies to daydream to alleviate feelings of shame.